Kehidupan Sosial dan Dinamika Domestik Keluarga di Timur Tengah: Sebuah Analisis Historis, Sosiokultural, dan Teoretis - Rio Chaniado Anggara; Mohammad Izdiyan Muttaqin; Muhammad Rafiuddin (AL-Ikhtiar : Jurnal Studi Islam, 2025)
This article examines the interconnection between macro-social developments and the dynamics of domestic family life in the Middle East, spanning from the pre-Islamic period to the contemporary era. Using a multidisciplinary approach that combines social science theory, cultural anthropology, and Islamic studies, this research examines the evolution of social structures, shifts in gender roles, and transformations in family fiqh practices. The primary focus is on the reforms introduced by Islam, as well as the impacts of modernization, globalization, and urbanization on both the nuclear family and extended family units. The study also integrates James Fowler’s theoretical perspective on the development of faith and Al-Ghazali’s philosophy on the nature of humanity to provide a holistic understanding of how spiritual and psychological dimensions shape social and domestic life patterns. This article contributes to the literature by presenting a concise evolutionary narrative that highlights the resilience and adaptability of Middle Eastern families.